A pesquisa em sustentabilidade e estrat??gia: a partir de um estudo bibliom??trico - Valentie, Luana da Silva Marques (2016)
Trough a Review In articles published in a 20-year period In the main high impact fator internationals Journals in Administration. The main motivation for this study is the apparent Lack of a review that links Strategy Value and sustainability. Although many researchers recognize the subject as a strategic challenge for companies, this study propose a better understanding in how ruestions regarding sustainability and the relation with strategy from bibliometric and citation cocitation study. The aim of this study is to comprehend the intellectual structure of the field of sustainability strategy studies, and be used to assist for future research agenda related to sustainability and strategy from a review of articles published in a period of 20 years in leading journals with high factor impact on management and sustainability, determine which topics studied in administration at this theme are being investigated, analyzing the structure of sustainability studies and strategy from bibliometric study of citation and co-citation. The question that guided the study was: What are the possibilities for future research related to sustainability and strategy? The research method was the bibliometric and data collection occurred in the Web of Science platform. According to the results, the publication of articles on sustainability has increased in the last five years. From a theoretical construct, further discussions can be generated, especially those that discuss the effects of the financial impact in promoting sustainable practices, and those who seek to analyze the balance between sustainability and competitive development of various sectors organizations. The most prominent issue was the CSR- Corporate Social Responsibility, as ethical and transparent management with their public , the analysis of the study, you can see that the RBV can present high potential explanatory opening different perspectives of strategic performance of individual company.